Mass Sports - Grigoryeva, Elena (project baikal, 2017)
Had there ever been any special sports buildings in our regional centers before the 20th century? And before the middle of the 20th century? In Irkutsk and Baikalsk there had not been any. They appeared during the Thaw of the 1960s. The buildings had innovative large-span structures and were unique. They were located in the city centers, forming important public spaces. They did not become obsolete within half a century. We begin our sport collection with them. Fitness has become one of the most popular kinds of the mass sport and has completely replaced the traditional “physical culture”. Dozens of variations of fitness and millions of participants pose a great challenge to contemporary architecture. The articles of our issue show the present and the future of architecture for fitness. We present a topical collection with a wide geographical range, including the Irkutsk Agglomeration, Tomsk, Krasnodar, sports in the Moscow Palace of Young Pioneers, and the anthology of the top foreign sports venues.